Case Report: Complete Remission With Anti−PD−1 and Anti−VEGF Combined Therapy of a Patient With Metastatic Primary Splenic Angiosarcoma - Xu, Weiran; Wang, Kai; Gu, Wenguang; Nie, Xinxin; Zhang, Hao; Tang, Chuanhao; Lin, Li; Liang, Jun (Frontiers in Oncology, 2022)
Primary splenic angiosarcoma (PSA) is a rare malignancy with a poor prognosis. At present, research on immunotherapy in PSA is relatively limited. We report the case of a patient with metastatic PSA who was treated with anti‑PD‑1 and anti‑VEGF combined therapy and achieved complete response (CR). The patient was a 57‑year‑old woman with three liver metastases. She was treated with seven cycles of toripalimab plus anlotinib. We performed PD-L1 immunohistochemistry and next-generation sequencing, and the PD-L1 tumor proportion score was 75%. Finally, she achieved CR after six cycles of the combined therapy regimen. No serious adverse events were detected. To the best of our knowledge, this is the first clinical evidence that anti-PD-1 plus anti-VEGF therapy might be a promising option for patients with metastasis of PSA. More clinical trials are needed to verify the conclusion.